Working to leave or living to work?: Employees' quality work life factors and its impact on turnover intention - Leonilo M. Cruz; Bea Teresa S. Sengco; Nuquie P. Gadin (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Turnover intentions should be seriously viewed by top management as it corresponds to actual action or decision of leaving the job. Employees' loss has detrimental effect on the performance and lucrativeness of the organization. If employees are satisfied with their quality of work life, turnover intentions can be prevented. Thus, this study was conducted to determine through a quantitative research design whether the quality of work life factors (development, participation, compensation, supervision, and working environment) has a negative impact on turnover intentions of employees in a select private Higher Education Institution (HEI) in the Philippines. Purposive sampling was utilized among 152 teaching and non-teaching employees who accomplished the questionnaire which includes the quality of work life factors scale and Turnover Intention Scale (TIS-6). Data were analyzed using descriptive analysis, Pearson correlation coefficient and multiple regression analysis. Findings revealed that quality of work life significantly predicts turnover intentions; however, it was found out that among the five factors, only development, compensation, and working environment were significant with turnover intentions. In addition, only compensation and work environment negatively predicted turnover intentions, while in contrast, development positively predicted turnover intentions of employees. In conclusion, when employees believe they are underpaid and work in a hazardous and unpleasant workplace, they are more likely to want to leave. The implications could provide information to management and the human resource department, allowing them to focus on key aspects that could minimize the institution's employee turnover rate. Finally, in order to reduce employee turnover, it is suggested that the institution focus on developing and implementing compensation and work environment policies and programs.